Implementation of Multicultural Education in Indonesia - Musawir Baihaqi (EDUTEC : Journal of Education And Technology, 2021)
This paper examines the implementation of multicultural education in Indonesia. Through the literature review approach, this article explores the concept of multicultural education, multicultural education paradigm, characteristics of multicultural education, as well as the typology of multicultural education. All these studies are intended to explore how the role of multicultural education is implemented in Indonesia which has a variety of ethnic, linguistic, cultural, and religious beliefs. The study also emphasized multicultural education as one of the keys to maintaining the frame of diversity so that there is no division and maintaining and respecting the differences that exist